Assimetria de custos no gerenciamento de resultados - Pereira, Nevison Amorim (2019)
The objective of this work was to verify the association between cost asymmetry levels and earnings management. The sample consists of 157 Brazilian publicly traded companies, totaling 1570 observations from 2008 to 2017. It used the Anderson, Banker and Janakiraman (2003) model to measure cost asymmetry and Roychowdhury’s (2006) model and Jones Modified to calculate earnings management. For data analysis, it used the multiple regression models (linear) and logit model (nonlinear). Regarding the results, initially, it was shown that part of the companies presented asymmetry in costs and that earnings management was confirmed in companies suspected of avoiding the announcement of losses incurred in the accounting period. Subsequently, it was shown that earnings management and cost asymmetry are negatively associated. However, this result was significant only for the real earnings management. It is noteworthy that higher levels of cost asymmetry are related to lower earnings management only in the industrial sector. Some explanations for this result are the high fixed cost structure of this sector and the personal incentives of managers according to the Agency Theory, which imply greater cost asymmetry. It concludes that companies that present cost asymmetry have lower earnings management by real activities, and the thesis that the asymmetric behavior of costs mitigates earnings management by real activities and accruals was partially confirmed since the relationship was not significant for accruals. One contribution of this research is to point out to users of accounting information that an analysis of corporate cost behavior can indicate whether managers are using earnings management to adjust profit.